Paper Bullets, the Cuban Cartel as a Weapon of Ideological Propaganda - Castro Madriz, José María (2021)
This article is an approach to the study of the Cuban poster as an ideological tool within the cultural Cold War, when the revolutionary image evolves with the various stages of the Cuban revolutionary movement. From the 1950s to the so-called special period, Cuban cartels have recurring themes such as the defense of national autonomy and peripheral armed conflicts between the socialist and capitalist blocs. As an introduction to the main topic, the analysis covers the work of well-known exponents of the political graphic movement and the propaganda function of OSPAAAL as a diffuser and ideological support to other revolutionary movements in Central America in the 1980s.